2018
DOI: 10.1159/000485933
|View full text |Cite
|
Sign up to set email alerts
|

Real-World Experience with Nintedanib in Patients with Idiopathic Pulmonary Fibrosis

Abstract: Background: Nintedanib, an oral tyrosine kinase inhibitor, has been shown to slow down the progression of idiopathic pulmonary fibrosis (IPF) in two randomised placebo-controlled trials by reducing the annual decline in forced vital capacity (FVC). However, real-world experience is limited. Objective: To assess the efficacy and safety of nintedanib in a large cohort of patients treated at a tertiary referral site for interstitial lung diseases. Methods: The records of patients with a confirmed diagnosis of IPF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
67
2
6

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 79 publications
(89 citation statements)
references
References 27 publications
14
67
2
6
Order By: Relevance
“…The panel agreed that hepatic transaminase and bilirubin levels should be measured before initiating treatment but would advocate repeating these measures every 4 weeks for the first 6 months of treatment, and every 3 months or as clinical needed thereafter. In a recent retrospective, observational real-world study conducted in Greece ( n = 94) liver toxicity was reported in 5.3% of subjects [21], while real-world studies in Germany ( n = 64) and the United Kingdom ( n = 187) have reported hepatic enzyme elevations in 1.6 and 9.6% of nintedanib-treated subjects respectively [22, 23]. In the majority of patients, these elevations are reversible with a dose reduction or short treatment interruption [15, 17].…”
Section: Hepatic Side Effects In Patients On Nintedanibmentioning
confidence: 99%
See 1 more Smart Citation
“…The panel agreed that hepatic transaminase and bilirubin levels should be measured before initiating treatment but would advocate repeating these measures every 4 weeks for the first 6 months of treatment, and every 3 months or as clinical needed thereafter. In a recent retrospective, observational real-world study conducted in Greece ( n = 94) liver toxicity was reported in 5.3% of subjects [21], while real-world studies in Germany ( n = 64) and the United Kingdom ( n = 187) have reported hepatic enzyme elevations in 1.6 and 9.6% of nintedanib-treated subjects respectively [22, 23]. In the majority of patients, these elevations are reversible with a dose reduction or short treatment interruption [15, 17].…”
Section: Hepatic Side Effects In Patients On Nintedanibmentioning
confidence: 99%
“…In a recent German real-life study that included a total of 64 patients treated with nintedanib, 43.7% of patients required concomitant antithrombot ic treatment; 28.1% received acetylsalicylic monother apy, 10.9% received anticoagulants (vitamin-K antagonist [VKA] or novel oral anticoagulant [NOAC]), and 4.7% received a combination of acetylsalicylic and anticoagulants. The mean follow-up period was 11 months (1 month minimum and 29 months maximum) and over the course of the study there was only 1 reported bleeding event, which occurred in a patient who was receiving a combination of acetylsalicylic and anticoagulant therapy [22]. …”
Section: Nintedanib Use In Patients With Additional Risk Factorsmentioning
confidence: 99%
“…Although increasing data on the real-life clinical experiences showing that nintedanib is an effective first-line therapy for IPF patients continue to emerge, only a few studies have investigated its safety and efficacy in patients switched from pirfenidone [5,11]. The data presented here suggest that nintedanib is a well-tolerated second-line therapy whose side effects are similar to those found in patients receiving it as a first-choice treatment.…”
Section: Discussionmentioning
confidence: 63%
“…Disease progression was evaluated on the basis of the patient's vital status and change in FVC (median and range); the latter was measured three times: The first time during the period the patient was taking pirfenidone 12 months prior to switching to nintedanib; the second, at the time the switch was made; and the third, 12 months after the patient initiated nintedanib treatment. An absolute decline in FVC predicted >5% within 12 months from nintedanib initiation was consistent with disease progression [11]. Moreover, the number of respiratory-related hospitalizations at the end of the follow-up period was evaluated in comparison with those recorded through the 12-month period prior to switching.…”
Section: Methodsmentioning
confidence: 91%
“…Real-world observational studies, on the other hand, also have major limitations and a multitude of biases that potentially skew conclusions, particularly if results are considered in isolation from RCTs. However, they do provide valuable evidence on how antifibrotics work in clinical practice, and which factors need to be included in clinical decision-making when faced with the uncertainty of an individual patient who does not fulfil the RCT inclusion criteria [11, 13-15]. …”
mentioning
confidence: 99%